(untitled) (Repertorio Científico, 2020)
The cultivation of pineapple (Anannas comosus L. var. comosus) is an important source of economic and employment in tropical and African countries. Despite the efforts that have been made by research centers, the number of varieties that have been produced and implemented in the last 100 years has not generated great variability of new genetic materials; in most cases they have been restricted to germplasm evaluations, their local use and have not generated varieties that can be adapted to other agro-ecological conditions. Objective: a review of biological and genetic aspects to be considered to carry out a genetic improvement project in pineapple is carried out, a proposal is also made in order to improve processes and achieve improvement objectives in a shorter time.